Management of sulphur for yield augmentation in rice (Oryza sativa) under rice fallow system - MISHRA, AMBIKA PRASAD; DASH, ASHISH KUMAR; PANDA, NARAYAN; PATTANAYAK, S K; PRUSTY, MEENAKHI; SAHU, SUMAN G (The Indian Journal of Agricultural Sciences, 2022)
Sulphur (S) is ranked as 4th most essential nutrient after nitrogen, phosphorous and potassium which plays a vital role in crop production. Its uses have declined in recent years. S-deficiency in soils of Odisha has increased from 36% during 2008–09 to 44% in 2018–19. A field experiment was conducted at farmers’ field in Ankurda village, Goindia block of Dhenkanal district, for two years (2018–19 and 2019–20) in order to study the effect of different sources of sulphur in rice (Oryza sativa L.) (cv. Swarna Sub 1) under mid-central table land zone of Odisha. The experiment was conducted in RBD with 10 treatments and 3 replications. Four different sources of sulphur (SSP, calcium sulphate, elemental S0 and navaratna as (20-20-0-13) were used with two methods, viz. basal and top dressing to rice crop during rainy (kharif) season. A mixture source was formulated with (CaSO4 + SSP) @1:1 ratio which was applied as basal only. Among the sources of sulphur applied, highest biomass yield was recorded with spilt method of ES which followed the order as: ESo>mixture source>navaratna>SSP>gypsum. Due to S fertilization, the biomass yield increased by 16% over the control (T1). Spilt application of sulphur fertilizer exerted a beneficial effect on yield attributing character, higher grain and straw yield, nutrient uptake, sulphur use efficiency and sulphur harvest index, quality parameters and B:C ratio of Swarna Sub-1 in comparison to basal application of fertilizers during rainy (kharif) season.